(Mardi Al-Radhi on the Kafiya Ibn Al-Hajib) by the Judge Hussain bin Moin Al-Maibdhi who died in the year 910 A.H. Investigation of the section on incomplete verbs (was and its derivative sisters) from plate 142 to plate 145 - Al-Dulaimi, Omar; Dahour, Ahmed (Islamic Sciences Journal, 2023)
Praise be to God who made us the best nation brought out to people and preferred us over all other races. We praise Him for having guided us to Islam and made us from a nation of the best of creatures, upon him be the best of prayers and the most complete peace and his family and all his companions, O God, we have no knowledge except what You taught us, that You are the All-Knowing, the Wise. Your mercy in your righteous servants. As for what follows: Heritage is the intellectual repository that has its roots in the depths of history in the East and the West, and much of that heritage still fills the roofs of libraries in various countries of the world. Many of them cast away in the darkness of libraries as a result of wars ans disasters, waiting for someone to shake the dust and shed light on them in order to benefit from them. This research aims to investigate Mardi al-Radhi on the Kafayah of Ibn al-Hajib” by Hussain bin Moin al-Maibdhi, who died in the year (910 AH): the chapter on incomplete acts (Kahn and her sisters) From the plate [142 / w] to the plate [145 / w], so this paper is divided into two parts: The first part: a description of the manuscript copies adopted in the investigation, and the investigation method: As for the second part: the verified text is presented, which is (Mardi al-Radhi on Kafiya Ibn al-Hajeb). Bab Kan and her sisters. Then the conclusion and highlighted the most important findings and recommendations, then concluded the research with a list of indexes of sources and references that it relied on in the investigation.